Muscular toxicity of colchicine combined with statins: a real-world study based on the FDA adverse event reporting system database from 2004–2023 - Liu, Ying; Wei, Chunyan; Yuan, Yanling; Zou, Dan; Wu, Bin (Frontiers in Pharmacology, 2024)
Background: Through an analysis of the Food and Drug Administration Adverse Event Reporting System (FAERS) of the FDA, we explored the signal strength of adverse reactions (ADRs) related to myopathy caused by the combination of colchicine and statins and gained insight into the characteristics of these myopathy related ADRs.We extracted data from the FAERS database about ADRs in individuals with myopathy resulting from the combination of colchicine and statins. The analysis was conducted for the period spanning from January 2004 to December 2023 using the reported odds ratio (ROR) and information component (IC) methods to assess muscle-related ADR signals.Results: A total of 18,386 reports of statin myopathy-associated adverse reactions, 348 colchicine myopathy-associated adverse reactions, and 461 muscle-associated adverse reactions due to the combination of the two were collected; the strongest signals of statin myotoxicity events were for